2010
DOI: 10.1097/mat.0b013e3181de0842
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of β2-Microglobulin Clearance on the Risk Factors of Cardiovascular Disease in Hemodialysis Patients

Abstract: beta2-Microglobulin (beta2M) is an independent predictor of outcome for hemodialysis (HD) patients and a representative substance of middle molecules. We tested the relationship among serum beta2M levels and cardiovascular disease (CVD) risk factors in HD patients. A total of 132 HD patients were divided according to the dialysis membrane used [property; cellulose and synthetic or beta2M clearance; low filtration (LF), middle filtration (MF), and high filtration (HF)]. There was no significant difference in CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…30,31 Furthermore, its serum levels are positively correlated with inflammatory variables 30 and inversely associated with circulating endothelial progenitor cell number. 31 These findings suggest that increased b 2 -MG could contribute to impaired endothelial cell repair, thus being involved in CVD in HD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Furthermore, its serum levels are positively correlated with inflammatory variables 30 and inversely associated with circulating endothelial progenitor cell number. 31 These findings suggest that increased b 2 -MG could contribute to impaired endothelial cell repair, thus being involved in CVD in HD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HMA ratios were significantly increased by treatment with pre-OL-HDF. We had reported that the β2-MG removal rate was significantly associated with risk factors of cardiovascular disease [17]. Furthermore, a previous study reported that higher serum levels of β2-MG (≥32.2 mg/L) were significant predictors of mortality in MHD patients, independent of HD duration, diabetes, malnutrition, or inflammation [18].…”
Section: Resultsmentioning
confidence: 99%
“…And serum beta2 microglobulin level was a significant predictor of mortality in hemodialysis patients, independent of hemodialysis duration, diabetes, malnutrition and chronic inflammation (Okuno et al, 2009). A few studies also supported the correlation between serum beta2 microglobulin levels and various cardiovascular risk factors, including CRP, in hemodialysis patients (Kuragano et al, 2010). And recently, beta2 microglobulin has been suggested to be a novel biomarker of peripheral arterial disease and an independent predictor of aortic stiffness in atherosclerosis, in the general population (Wilson et al, 2007).…”
Section: Beta 2 Microglobulinmentioning
confidence: 96%